LIVESTOCK COMPOSITION AND MEAT DIET OF THE POST-DOLMEN PEOPLE OF THE FOOTHILLS OF THE NORTH-WESTERN CAUCASUS (ACCORDING TO THE SHUSHUK SETTLEMENT DATA) - Erlih, Vladimir Roal'dovic; Spasovskij, Urij Nikolaevic; Godizov, Georgij Leonidovic (History, Archeology and Ethnography of the Caucasus, 2019)
This article presents the results of the archaeozoological study of bone material from the dig with kitchen utensils of the Shushuk settlement in the foothills of Adygea (final of the late Bronze Age, post-dolmen horizon) - 692 definable fragments. Based on their analysis, the authors conclude that the livestock economy of the post-dolmen people was of a home-based, pasture-stall nature. Cattle is dominant (more than 60% of bones), followed by pigs, while sheep and goats make up only a small percent of the material - about 10%. Hunting did not play a significant role in this society. The horse found in the upper layers can be attributed to steppe influence. By comparing the composition of the Shushuk livestock with available data from Early and Middle Bronze Age settlements in the region, the researchers conclude that the overall composition of the Shushuk livestock bears a close resemblance to that of the Daguak-Dakhovsky settlement, which belongs to the Middle Bronze Age (dolmen culture). The analysis also takes into account comparative data on the livestock composition of contemporary steppe cultures (e.g. Belozersk and Kobyakovsk ones in the Lower Don) in which horses already played a significant role. The authors also attempt to trace the dynamic of change in livestock composition over time as represented by the chronological horizons (i.e. spits).